2014
DOI: 10.1016/j.vaccine.2013.11.062
|View full text |Cite
|
Sign up to set email alerts
|

DNA vaccination against a fish rhabdovirus promotes an early chemokine-related recruitment of B cells to the muscle

Abstract: a b s t r a c tIn fish, intramuscular (i.m) injection of plasmid DNA encoding viral proteins has proved a highly effective vaccination strategy against some viral pathogens. The efficacy of DNA vaccination in teleost fish is based on the high level of viral antigen expression in muscle cells inducing a strong and long-lasting protection. However, the mechanisms through which this protection is established and effectuated in fish are still not fully understood. Moreover, similarities to mammalian models cannot … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 49 publications
0
32
0
2
Order By: Relevance
“…Trout IgT2 was primarily expressed in the systemic lymphoid organs, like zebrafish IgZ1. This phenomenon may suggest the functional difference between these two IgT subclasses as well as the non-mucosal role for IgT (Castro et al, 2013, 2014; Castro and Tafalla, 2015). In addition, combined with the previous studies about trout IgT + B cells in various mucosal tissues during homeostatic conditions (Xu et al, 2013, 2016; Zhang et al, 2011), it seems that there are more IgT + B cells and IgT transcripts in gill than gut and skin.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Trout IgT2 was primarily expressed in the systemic lymphoid organs, like zebrafish IgZ1. This phenomenon may suggest the functional difference between these two IgT subclasses as well as the non-mucosal role for IgT (Castro et al, 2013, 2014; Castro and Tafalla, 2015). In addition, combined with the previous studies about trout IgT + B cells in various mucosal tissues during homeostatic conditions (Xu et al, 2013, 2016; Zhang et al, 2011), it seems that there are more IgT + B cells and IgT transcripts in gill than gut and skin.…”
Section: Discussionmentioning
confidence: 98%
“…IgT plays important roles in mucosal immunity in the gut (Zhang et al, 2010), skin (Xu et al, 2013) and gill (Xu et al, 2016) in rainbow trout ( Oncorhynchus mykiss ). In addition, recent studies indicated that IgT + B cells also participate in the responses against viral infections (Castro et al, 2013) and DNA vaccination (Castro et al, 2014). These evidences indicate that teleost IgT is also involved in systemic immunity (Castro and Tafalla, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…DNase I-treated total RNA was prepared from tissue samples using a combination of Trizol (Invitrogen) and an RNAeasy Mini kit (Qiagen) as described previously [32]. Total RNA was eluted from the columns in RNase-free water, quantified using a Nanodrop 1000 spectrophotometer (Thermo Scientific) and stored at -80°C.…”
Section: Methodsmentioning
confidence: 99%
“…However, no further characterization of the lymphocytes registered in these studies was reported. In addition, the type of vaccine used for injection might also be of significance, as reported by Castro et al (), where intramuscularly immunized rainbow trout ( Oncorhynchus mykiss L.) showed early recruitment of high levels of B lymphocytes (both IgM + and IgT + ) into the muscle, when injected with a DNA vaccine against VHSV, while fish injected with complete Freund's adjuvant mainly showed infiltration of granulocyte‐/monocyte‐type cells. Our results are in agreement with several of these authors’ observations, although it is uncertain whether the amount of IgM + cells would remain stable or increase/decrease as the inflammation progressed further beyond the time range of this study.…”
Section: Discussionmentioning
confidence: 90%